The Effectiveness of Using Wakelet in Improving Senior High Students’ Descriptive Text Writing - Pebsrikova, Bunga Basyaasya; Akhiriyah, Suvi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This study aims to examine the effectiveness of using Wakelet as a media to improve senior high school students' descriptive text writing skills. The research was conducted at one of senior high school in East Java, focusing on tenth-grade students. A quasi-experimental design was employed, involving two groups: an experimental group who is using Wakelet and a control group. Data collection was performed through pre-tests and post-tests to assess the students' writing performance. The results were analyzed using statistical methods, including independent sample t-tests. The findings indicated a significant improvement in the descriptive text writing skills of students who used Wakelet compared to the control class who did not. The mean score of the experimental group was notably higher (sig. value 0.013 < 0.05) than that of the control group. This research demonstrates that Wakelet is an effective tool for teaching descriptive text writing (? = 0.076). It provides an interactive and engaging platform that enhances students’ writing skill. The study suggests that educators consider integrating Wakelet into their teaching practices to improve writing skills.